Probing elastic anisotropy of human skin in vivo with light using non-contact acoustic micro-tapping OCE and polarization sensitive OCT - Kirby, Mitchell A.; Tang, Peijun; Liou, Hong-Cin; Kuriakose, Maju; Pitre, John J.; Pham, Tam N.; Ettinger, Russell E.; Wang, Ruikang K.; O’Donnell, Matthew; Pelivanov, Ivan (Scientific reports, 2022)
Skin broadly protects the human body from undesired factors such as ultraviolet radiation and abrasion and helps conserve body temperature and hydration. Skin’s elasticity and its level of anisotropy are key to its aesthetics and function. Currently, however, treatment success is often speculative and subjective, and is rarely based on skin’s elastic properties because there is no fast and accurate non-contact method for imaging of skin’s elasticity. Here we report on a non-contact and non-invasive method to image and characterize skin’s elastic anisotropy. It combines acoustic micro-tapping optical coherence elastography (AμT-OCE) with a nearly incompressible transversely isotropic (NITI) model to quantify skin’s elastic moduli. In addition, skin sites were imaged with polarization sensitive optical coherence tomography (PS-OCT) to help define fiber orientation. Forearm skin areas were investigated in five volunteers. Results clearly demonstrate elastic anisotropy of skin in all subjects. AμT-OCE has distinct advantages over competitive techniques because it provides objective, quantitative characterization of skin’s elasticity without contact, which opens the door for broad translation into clinical use. Finally, we demonstrate that a combination of multiple OCT modalities (structural OCT, OCT angiography, PS-OCT and AμT-OCE) may provide rich information about skin and can be used to characterize scar.